Research on protection technology for location privacy in VANET - Jian-ming ZHANG; Yu-juan ZHAO; Hao-bin JIANG; Xue-dan JIA; Liang-min WANG (Tongxin xuebao)
Location-based services in VANET solved the problem of road safety,and provided the convenient services to drivers and passengers.But it also brought new problems of privacy protection.The content of privacy protection was analyzed,and put emphasis on two kinds of privacy protection technology based on pseudonyms and signature respectively.Pseudonym-based schemes were classified as special-area based,silence-period,cryptographic mix-zones and mix-zones communication proxy based schemes.Signature-based schemes were also divided into two classes:group-signature and ring-signature.The evaluation methods for privacy protection level were surveyed,in which anonymity set,entropy metric,mathematical analysis theory and formal analysis were discussed and compared.